In this grave hour [large type] : a novel - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel, 2017)
When listeners last heard Maisie Dobbs, it was 1938, and the world was on the brink of war. Maisie herself was on a dangerous mission inside Nazi Germany, where she encountered an old enemy and the Fuhrer himself. In In This Grave Hour, a year has passed, and Maisie is back home in England - yet neither she nor her nation is safe. Britain has just declared war on Germany and is mobilizing for the devastating battle ahead. But when she stumbles on the deaths of a group of refugees, Maisie suspects the enemy may be closer than anyone knows.